Experimental use of flow cytometry to detect bacteria viability after hyperbaric oxygen exposure: Work in progress report - Rozloznik, Miroslav; Lochmanova, Alexandra; Chmelar, Dittmar; Hajek, Michal; Korytkova, Karin; Cisarikova, Monika (Diving and hyperbaric medicine, 2020)
INTRODUCTION: Hyperbaric oxygen treatment (HBOT), based on inhaling pure oxygen under elevated ambient pressure, is used as adjuvant intervention to promote healing in infected wounds. Despite extensive clinical evidence of beneficial effects of HBOT in soft tissue infections the mechanism of action remains to be elucidated. The aim of this study was to evaluate the use of flow cytometry as a novel method to assess the viability of pathogenic bacteria after hyperbaric oxygen (HBO) exposure. METHODS: Bacterial strains associated with soft tissues infections: Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus were exposed to oxygen at 2.8 atmospheres absolute (atm abs) (283.6 kPa) pressure for 45, 90, or 120 min, then stained with propidium iodide and thiazole orange and analysed by flow cytometry. RESULTS: Escherichia coli and Staphylococcus aureus showed no change in viability, nor morphology, the viability of Pseudomonas aeruginosa reduced in a dose-dependent manner and Klebsiella pneumoniae also showed dye uptake after HBO. CONCLUSIONS: These initial results, indicate diverse sensitivity of bacteria to HBO, and suggest that flow cytometry can be used to monitor viability and morphological changes triggered by HBO exposure in bacteria.
Keywords: výzkumná zpráva; Research Report; Oxygen; průtoková cytometrie; kyslík; Hyperbaric Oxygenation; Bacteria; Flow Cytometry; hyperbarická oxygenace; mikrobiální viabilita; Microbial Viability